From Hacking to Report Writing An Introduction to Security and Penetration Testing - Svensson, Robert (Apress : Imprint: Apress, 2016)
Learn everything you need to know to become a professional security and penetration tester. You will learn how to easily find vulnerabilities and misconfigurations as each step of the process is broken down and simplified. You also will learn how to methodically locate, exploit, and professionally report security weaknesses using techniques such as SQL-injection, denial-of-service attacks, and password hacking. From Hacking to Report Writing gives you the technical know-how you need to carry out advanced security tests and also provides insight into crafting professional reports that describe your work and how your customers can benefit from it. The book gives you the tools you need to clearly communicate the benefits of high-quality security and penetration testing to IT management, executives, and other stakeholders. We live in a time where computer security is more important than ever. Staying one step ahead of hackers has never been a bigger challenge. From Hacking to Report Writing clarifies how you can sleep better at night knowing that your systems have been thoroughly tested for security weaknesses. On-the-job stories are included to show you how to apply what you have learned to real-world situations. With this book you will know: • Why security and penetration testing is important • How to find vulnerabilities in any system using the same tools and techniques used by hackers • How to write professional reports • Which security and penetration testing method to apply for any given situation • How to successfully hold together a security and penetration test project.